ANÁLISIS DEL CONSUMO ENERGÉTICO EN CONJUNTOS RESIDENCIALES MEDIANTE LA IMPLEMENTACIÓN DE TECNOLOGÍAS SMART HOME EN LA CIUDAD DE QUEVEDO - LABORDE NÚÑEZ, CRISTHIAN BRADT (2025)
This research project analyzes energy consumption in residential complexes in the city of Quevedo, aiming to identify sustainable solutions in response to the growing use of electronic devices and household appliances